2020
DOI: 10.2217/pme-2020-0103
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Circular RNAs in Therapy Resistance of Patients With Solid Tumors

Abstract: Circular RNAs (circRNAs) are a type of single-stranded RNA molecules forming a covalently closed, continuous structure, lacking 5′-3′ polarity and polyadenylated tails. Recent advances in high-throughput sequencing technologies have revealed that these molecules are abundant, resistant to degradation and often expressed in a tissue- or developmental stage-specific manner. circRNAs are produced by back-splicing circularization of primary transcripts and exhibit a variety of functions, including regulation of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 140 publications
1
35
0
1
Order By: Relevance
“…In several instances, the involvement of circRNAs in the deregulation of signal transduction has been evidenced, supporting the key role of circRNAs in cancer initiation, progression, metastasis, stemness, and resistance to therapy [ 35 ]. More specifically, circRNAs can regulate the cell cycle by exerting their sponging ability; for instance, circ-ZNF292 inhibits cell proliferation and promotes apoptosis of hepatocellular carcinoma cells by regulating the WNT/β-catenin pathway [ 36 ].…”
Section: Functions Of Circrnas and Their Involvement In Signal Transductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In several instances, the involvement of circRNAs in the deregulation of signal transduction has been evidenced, supporting the key role of circRNAs in cancer initiation, progression, metastasis, stemness, and resistance to therapy [ 35 ]. More specifically, circRNAs can regulate the cell cycle by exerting their sponging ability; for instance, circ-ZNF292 inhibits cell proliferation and promotes apoptosis of hepatocellular carcinoma cells by regulating the WNT/β-catenin pathway [ 36 ].…”
Section: Functions Of Circrnas and Their Involvement In Signal Transductionmentioning
confidence: 98%
“…Considering the multiple biological functions of circRNAs, it is not surprising that numerous researchers have focused on elucidating their distinct properties. For this reason, their implication in the regulation of aberrant signaling, cancer onset, progression, and therapy resistance has repeatedly been demonstrated [ 16 , 35 ], and the most promising areas for future research are shown in Figure 7 . The immense potential of highly expressed circRNAs as novel, non-invasive biomarkers has righteously kept them in the spotlight; circulating circRNAs are enriched in body fluids, such as blood, saliva, plasma, and serum, and there are several circRNAs found in exosomes that can affect the tumor microenvironment and malignancy of cancer cells [ 122 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…circRNAs modulate gene expression by various mechanisms, including functioning as miRNA sponges, RNA-binding protein (RBP) sponges, transcription regulators, and templates for translating peptides [ 37 , 43 , 44 ]. ciRS-7 (also known as CDR1as ), the first miRNA sponge to be identified, is well known for sponging miR-7 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the era of individualized and precision medicine, robust molecular markers are required to ameliorate therapeutic decisions [34,35]. The integration of diagnostic, prognostic, and predictive molecular markers revolutionizes the field of modern oncology by providing tailored therapeutic management [36][37][38]. As already mentioned, miRNAs regulate gene expression at the transcriptional and post-transcriptional levels.…”
Section: Discussionmentioning
confidence: 99%